The Status of Setaria viridis Transformation: Agrobacterium-Mediated to Floral Dip - Van Eck, Joyce (Frontiers in Plant Science, 2018)
Setaria viridis has many attributes, including small stature and simple growth requirements, that make it attractive as a model species for monocots. Genetic engineering (transformation) methodology is a key prerequisite for adoption of plant species as models. Various transformation approaches have been reported for S. viridis including tissue culture-based and in planta by Agrobacterium tumefaciens infection of floral organs referred to as the floral dip method. The tissue culture-based method utilizes A. tumefaciens infection of mature seed-derived callus with subsequent recovery of stable transgenic lines. Vectors found to be most effective contain the hygromycin phosphotransferase selectable marker gene driven by either Panicum virgatum or Zea mays ubiquitin promoters. As for the floral dip method, there are two reports based on Agrobacterium infection of young S. viridis inflorescences. Plants were allowed to mature, seeds were collected, and analysis of the progeny verified the presence of transgenes. Each transformation approach, tissue culture based and floral dip, has advantages and disadvantages depending on the expertise of personnel and resources available. While the tissue culture-based method results in a higher transformation efficiency than floral dip, implementation requires a specific technical skillset that limits availability of experienced personnel to successfully perform transformations. Less technical experience is required for floral dip, however, a lack of high quality growth chambers or greenhouses that provide the necessary optimum growing conditions would reduce an already low transformation efficiency or would not result in recovery of transgenic lines. An overview of transformation methods reported for S. viridis are presented in this review.